2021
DOI: 10.1177/10283153211061433
|View full text |Cite
|
Sign up to set email alerts
|

“It's Doable”: International Graduate Students’ Perceptions of Online Learning in the U.S. During the Pandemic

Abstract: This study aims to understand the learning experiences and challenges of international students enrolled in Master's and PhD programs in various institutions who were forced to transition to online learning during the pandemic. In particular, the study explores the experiences and perceptions of seven non-native English-speaking international graduate students who came from six different countries and studied at different schools of education through phenomenological interviews. Analysis yields insight into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Research that draws a comparative analysis between international and domestic college students in the U.S. is limited ( Han et al, 2022 ; Li & Che, 2022 ), though there are some studies that have examined this aspect outside of the U.S. ( Cranfield et al, 2021 ; Demuyakor, 2020 ). For example, Demuyakor (2020) examined the perception of online learning in China by international (Ghanaian) students: most were pleased with the effectiveness and credibility of online course content, but they mentioned two drawbacks: the lack of social interaction and high cost of internet data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that draws a comparative analysis between international and domestic college students in the U.S. is limited ( Han et al, 2022 ; Li & Che, 2022 ), though there are some studies that have examined this aspect outside of the U.S. ( Cranfield et al, 2021 ; Demuyakor, 2020 ). For example, Demuyakor (2020) examined the perception of online learning in China by international (Ghanaian) students: most were pleased with the effectiveness and credibility of online course content, but they mentioned two drawbacks: the lack of social interaction and high cost of internet data.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Han et al (2022) interviewed 7 international graduate students in U.S. institutions. While professors helped students cope with the pandemic transition, students felt professors were more accessible in person than online.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Large-scale quantitative assessments have identified that international students were under social, emotional, academic, and discrimination stresses (Soria and Horgos, 2021;Gao et al, 2022). Many qualitative research further pinpoint that international students face limited opportunities to interact with family, peers, and faculty members and therefore need to secure transnational support (Wang and DeLaquil, 2020;Han et al, 2021;Hari et al, 2021;Hu et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic brought about challenges and difficulties to international students. Studies reported that international students are likely to suffer from psychological and emotional problems, which in turn negatively affect their learning [39][40][41]. In addition, an increasing number of studies have investigated the challenges of emergency online foreign language classes in the pandemic [42][43][44][45][46][47][48][49].…”
Section: Online Learning Environmentmentioning
confidence: 99%
“…Previous research on international students in degree courses reported negative influences of online environments on academic studies during the pandemic [39][40][41]. This research focused on the participants in online language courses designed specifically for international students to gain accuracy in pronunciation and fluency of speaking, understand spoken Chinese, and consolidate grammar.…”
Section: Rq 1: Characteristics Of International Students' Online Chin...mentioning
confidence: 99%